Fiscal Multipliers and the State of the Economy - Baum, Anja (IMF Working Papers; Working Paper ;, 2012)
Only a few empirical studies have analyzed the relationship between fiscal multipliers and the underlying state of the economy. This paper investigates this link on a country-by-country basis for the G7 economies (excluding Italy). Our results show that fiscal multipliers differ across countries, calling for a tailored use of fiscal policy. Moreover, the position in the business cycle affects the impact of fiscal policy on output: on average, government spending, and revenue multipliers tend to be larger in downturns than in expansions. This asymmetry has implications for the choice between an upfront fiscal adjustment versus a more gradual approach.